Aerial geology : a high-altitude tour of North America's spectacular volcanoes, canyons, glaciers, lakes, craters, and peaks - Morton, Mary Caperton (Timber Press, 2017)
Aerial Geology is an up-in-the-sky exploration of North America's 100 most spectacular geological formations. Crisscrossing the continent from the Aleutian Islands in Alaska to the Great Salt Lake in Utah and to the Chicxulub Crater in Mexico, Mary Caperton Morton brings you on a fantastic tour, sharing aerial and satellite photography, explanations on how each site was formed, and details on what makes each landform noteworthy. Maps and diagrams help illustrate the geological processes and clarify scientific concepts.